CONTRIBUTION OF RURAL WOMEN IN THE FARM PRODUCTIVITY - M. Ashfaq; H. Ashiq; I. A. Baig; A. Saghir (Journal of Animal and Plant Sciences, 2008)
Women’s role as farmers as well as wage laborers has often been ignored. The main reason is the non-availability of reliable statistics on the actual size and sex composition of the agricultural work force. Women participation in day-to-day farm and off farm activities is very extensive. The main objective of this paper was to study and quantify the share of women in household’s farm income and productivity of wheat crop in Faisalabad district. Multiple linear regression model was used to analyze the data. The results of the study showed that area under wheat crop, quantity of seed, quantity of fertilizer and female working hours were significant variables that contributed towards the productivity of wheat. Female working hours were also having positive impact on the overall income of the farm households.
Keywords: Farm productivity; women’s contribution; analysis.